Perang Melawan Bahaya Hoaks COVID-19 di Dunia - Ridwan Balatif (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is the cause of the Coronavirus Disease 2019 (COVID-19) pandemic. As of February 28, 2021, around 113 million people have confirmed COVID-19 globally. One of the things that hampers the handling of COVID-19 both globally and in Indonesia is the result of the large number of hoaxes circulating about COVID-19. The purpose of this article is written to increase understanding of the circulating COVID-19 hoaxes and the spirit of education against hoaxes related to COVID-19. About 89% of hoaxes circulating on various social media are rumors, 7.8% are in the form of conspiracy theories and the rest are in the form of stigma. This circulating hoax can harm others, such as information that alcohol can kill the corona virus in the body. As a result of this information, 44 Iranians have died from alcohol poisoning which is believed to kill the corona virus. In addition, the existence of hoaxes such as